The “tramezzo” in Early Franciscan Churches in Italy - Kovalchuk, Lada I. (Actual Problems of Theory and History of Art, 2019)
The article offers an analysis of specific building practices and church planning of Early Franciscans. It focuses on the issues of a significant liturgical transformation within the Roman Church and the Order itself, which began in the second half of the 13th century. The author analyzes the phenomenon of chancel barriers of Late Medieval and Early Renaissance Franciscan churches in Italy. Along with providing a brief overview on possible reconstruction of decoration and architectural forms of the “tramezzi”, this paper draws attention to its significance within the spatial hierarchy and liturgical cursus of the Friars. The article also considers some pivotal turns and perspectives of modern historiography, which are generally devoted to the principles of interior divisions and limitations in the Christian sacred architecture as a whole.
Keywords: the Franciscans; the tramezzo; altar; choir; gothic architecture in Italy; architecture of the Franciscan Order